2005
DOI: 10.1055/s-2005-871302
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Flavonoids fromSophora flavescensto the Rat Uterine Estrogen Receptor

Abstract: Prenylflavonoids and lavandulylflavonoids were isolated from the roots of Sophora flavescens Aiton (Fabaceae). The ability of 8-prenylkaempferol (1), kushenol X (2), norkurarinone (3), leachianone A (4), kushenol C (5), maackiain (6) and a root-extract of S. flavescens to displace 17beta-estradiol (E2) from rat uterine estrogen receptor (ER) was determined. Relative binding affinities (RBA) of prenylated flavonoids were weak with RBA values between 0.004 and 0.072. A lavandulyl or prenyl group at the position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Although the prenylated flavonoids did not affect P450 activities, kurarinone has been reported to exhibit weak estrogenic activity (De Naeyer et al, 2004). A minor ingredient, 8-prenylnaringenin, has been reported to show moderate estrogen receptor-binding affinity in rat uterus (Hillerns and Wink, 2005). Our findings revealed that ingestion of extracts 1 and 2, but not extract 3 caused the gender-relative induction of Cyp2a and Cyp3a.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although the prenylated flavonoids did not affect P450 activities, kurarinone has been reported to exhibit weak estrogenic activity (De Naeyer et al, 2004). A minor ingredient, 8-prenylnaringenin, has been reported to show moderate estrogen receptor-binding affinity in rat uterus (Hillerns and Wink, 2005). Our findings revealed that ingestion of extracts 1 and 2, but not extract 3 caused the gender-relative induction of Cyp2a and Cyp3a.…”
Section: Discussionmentioning
confidence: 68%
“…The methanol extract of S. flavescens showed estrogenic activity in Ishikawa cells (Yoo et al, 2005). Prenylated flavonoids of S. flavescens, 8-prenylnaringenin and kurarinone, have been reported to show moderate estrogen receptor-binding affinity in rat uterus and exhibit estrogenic activity in Ishikawa cells, respectively (De Naeyer et al, 2004;Hillerns and Wink, 2005). However, the effects of S. flavescens on P450s and the sexual difference in the induction of P450s by S. flavescens have not been reported.…”
mentioning
confidence: 89%
“…Most of the remaining compounds were all structurally related 8-lavandulyl flavonoids (Fig. 2) which were identified as kushenol H (1) (Son et al, 2003), kushenol K (2) (Shin et al, 2002), kurarinol (5) , kushenol N (8) (Son et al, 2003), neokurarinol (10) (Kyogoku et al, 1973), kushenol C (11) (Hillerns & Wink., 2005), sophoraflavanone G (12) , leachianone A (13) (Kyogoku et al, 1973), kuraridine (14) , and kushenol A (15) by comparison of their MS, UV, and NMR spectra with published reference data. Other residual compounds were characterized as calycosin (3) and isoxanthohumol (7) , respectively.…”
Section: Chemical Characterizationmentioning
confidence: 98%
“…However, a lavandulyl or prenyl group at position 8 on the flavonoids could enhance binding to the rat uterine ER (Fig. 12) [10]. …”
Section: Soy-based Formulasmentioning
confidence: 99%